Immune Evaluation of Recombinant Lactobacillus plantarum With Surface Display of HA1-DCpep in Mice - Niu, Hui; Xing, Jun-Hong; Zou, Bo-Shi; Shi, Chun-Wei; Huang, Hai-Bin; Jiang, Yan-Long; Wang, Jian-Zhong; Cao, Xin; Wang, Nan; Zeng, Yan; Yang, Wen-Tao; Yang, Gui-Lian; et al. (Frontiers in Immunology, 2021)
Avian influenza viruses can be efficiently transmitted in mucous membranes, and conventional vaccines are not effective in protecting against mucosal infection by influenza viruses. To induce multiple immune responses in an organism, we constructed recombinant Lactobacillus plantarum expressing the influenza virus antigen HA1 with the adjuvant DCpep. The recombinant Lactobacillus plantarum strains NC8Δ-pWCF-HA1 and NC8Δ-pWCF-HA1-DCpep were used to immunize mice via oral administration, and the humoral, cellular and mucosal immune responses were evaluated. In addition, the serum levels of specific antibodies and hemagglutination inhibition (HI) levels were also measured. Our results showed that recombinant Lactobacillus plantarum activated paired lymph node dendritic cells, increased the numbers of CD4+IFN-γ+ and CD8+IFN-γ+ cells in the spleen and mesenteric lymph nodes, and affected the ability of CD4+ and CD8+ cells to proliferate in the spleen and mesenteric lymph nodes. Additionally, recombinant Lactobacillus plantarum increased the number of B220+ IgA+ cells in Peyer’s patches (PPs) and the expression of IgA in the lungs and different intestinal segments. In addition, specific IgG1 and IgG2a antibodies were induced at high levels in the mouse serum, and HI potency was significantly increased. Thus, the recombinant Lactobacillus strains NC8Δ-pWCF-HA1 and NC8Δ-pWCF-HA1-DCpep have potential as vaccine candidates for avian influenza virus.